2007
DOI: 10.1038/sj.npp.1301565
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic and Glutamatergic Regulation of Effort- and Delay-Based Decision Making

Abstract: Cost/benefit decisions regarding the relative effort or delay costs associated with a particular response are mediated by distributed dopaminergic and glutamatergic neural circuits. The present study assessed the contribution of dopamine and NMDA glutamate receptors in these different forms of decision making using novel effort-and delay-discounting procedures. In the effort-discounting task, rats could either emit a single response on a low-reward lever to receive two pellets, or make 2, 5, 10, or 20 response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

36
399
7
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 378 publications
(449 citation statements)
references
References 48 publications
36
399
7
3
Order By: Relevance
“…In line with this view, animal studies measuring dopamine efflux using microdialysis have shown contributions of the PFC and striatum in integrating reward, delay and uncertainty signals (St Onge et al, 2012), and pharmacological disruption of dopamine signaling produces effects on reward-driven behavior (Floresco et al, 2008). A role of striatal D2-type receptors in prefrontal cortical function has been inferred from rates of glucose metabolism (Volkow et al, 2001), and it has been proposed that abnormal activity of dopaminergic neurons may enhance stimulusreward associations (Wise, 2002) and the inhibition of reward-seeking behavior depends upon activity in corticostriatal projections (Jentsch and Taylor, 1999).…”
Section: Discussionmentioning
confidence: 80%
“…In line with this view, animal studies measuring dopamine efflux using microdialysis have shown contributions of the PFC and striatum in integrating reward, delay and uncertainty signals (St Onge et al, 2012), and pharmacological disruption of dopamine signaling produces effects on reward-driven behavior (Floresco et al, 2008). A role of striatal D2-type receptors in prefrontal cortical function has been inferred from rates of glucose metabolism (Volkow et al, 2001), and it has been proposed that abnormal activity of dopaminergic neurons may enhance stimulusreward associations (Wise, 2002) and the inhibition of reward-seeking behavior depends upon activity in corticostriatal projections (Jentsch and Taylor, 1999).…”
Section: Discussionmentioning
confidence: 80%
“…The results from the present study do offer some insight into the consequences of the neurobiological differences between LCRs and HCRs. Because the DAT is a primary pharmacological target of AMPH, and alterations in DA signaling are important for behavior in the delay-discounting task (Floresco et al, 2007;van Gaalen et al, 2006), the differential effects we observed for AMPH in LCRs compared to HCRs are a likely reflection of known differences in DAT function between these phenotypes (Sabeti et al, 2003;Briegleb et al, 2004). Importantly, impulsive choice behavior may be influenced by an interaction between DAergic and 5-HTergic function (Winstanley et al, 2005(Winstanley et al, , 2006b, and this could be relevant for differences in choice behavior between LCRs and HCRs.…”
Section: Discussionmentioning
confidence: 99%
“…The specificity of the dopamine contribution to decision making is underpinned by the demonstration of a double dissociation of changes in effort vs delay discounting following the administration of the mixed D 2 receptor antagonist, haloperidol and para-chlorophenylalanine (pCPA), indicating greater involvement of the D 2 family of receptors in the former and of serotonin activity in the latter forms of behavioral choice (Denk et al, 2005). In addition, the influence of dopamine upon these forms of decision-making function is likely to involve complex interactions with other neurotransmitter systems, such as glutamate, that also play a pivotal role in motivation and reinforcement (Floresco et al, 2008).…”
Section: Dopamine and Decision Makingmentioning
confidence: 99%